A bloodless technique for correction of equinovarus deformities by Taylor spatial frame: a prospective case series. Issue 1 (January 2021) - Meselhy, Mohammed Anter; Adawy, Adel H.; Halawa, Abdelsamie M.
Abstract : Background: Rigid ankle and foot deformities as a sequela of relapsed talipes equinovarus or vascular or neurological disorders are a challenge for orthopedic surgeons. This study introduces a bloodless technique to correct the deformities of the ankle in patients with these disorders using the Taylor Spatial Frame (TSF). Methods: Eighteen feet in 18 patients with equinovarus deformities were prospectively enrolled in this study. All patients underwent preoperative clinical evaluation that included neurovascular assessment. Deformity components were measured using a goniometer. All patients had gradual correction of the rigid equinovarus ankle and foot by TSF without any soft-tissue or bony procedures. Preoperative and postoperative ankle and foot equinus and varus angles, in association with the American Orthopaedic Foot and Ankle Society (AOFAS) score, were used for assessment of the functional outcome. Results: There were 13 male patients (72.2%) and five female patients (27%). The mean age of the patients was 25.89 (range 14 to 43, SD 7.28) years. The right side was affected in 11 patients (61.1%), and left side was affected in seven patients (38.9%). At the final follow-up the average AOFAS ankle hindfoot scores improved from 25.17 (range 12 to 39, SD 9.91) preoperatively to 74.78 (range 48 to 88, SD 15.33) postoperatively, ( t =22.13, P <0.001). Fifteen patients (83.3%) were categorized as "good", and three patients (16.7%) were categorized as "fair". Conclusions: TSF is a safe, effective, and simple method of correcting rigid equinovarus deformities of the ankle without soft-tissue releases or bone osteotomies and is a bloodless technique. Level of Evidence: Level IV.